(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
Acute and chronic toxicity was studied on individuals of the globally widespread Crustacean species Daphnia magna. The first batch of individuals was obtained from some nearby freshwater times and acclimatized in the laboratory in preparation for conducting a series of laboratory experiments on them. In which the time required to kill half of the experimental subjects was determined after 24 and 48 hours, respectively.Some biological characteristics of the species were studied, sush as the longitudinal, width and weight growth rate and the female’s life span under the influence of different graded concentrations of the pesticide Dimethoate , which is (10, 40, 60, 80, 100, 500 µg/l). The experiments continued from 28/11/2022 until 6/9/2023. The results showed that the longitudinal, transverse, and weight growth gradually decreased, and mortality rates increased directly with icreasing concentrations.